2012
DOI: 10.1086/bblv223n2p192
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Cement Apparatus and the Cement of the Buoy Barnacle Dosima fascicularis (Crustacea, Cirripedia, Thoracica, Lepadidae)

Abstract: Barnacles produce a proteinaceous adhesive called cement to attach permanently to rocks or to other hard substrata. The stalked barnacle Dosima fascicularis is of special interest as it produces a large amount of foam-like cement that can be used as a float. The morphology of the cement apparatus and of the polymerized cement of this species is almost unknown. The current study aims at filling these gaps in our knowledge using light and electron microscopy as well as x-ray microtomography. The shape of the cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The holdfast system of the barnacle differs from that of mytilid mussels and sabellariid polychaetes by the lack of a detectable L-DOPA system and the slow curing process of the adhesive (Naldrett 1993;Kamino et al 1996;Kamino 2010;Nicklisch & Waite 2012). Barnacle cement is produced by unicellular glands throughout the lifetime of the animal in accordance with its moulting cycle Fyhn & Costlow 1976;Jonker et al 2012;Zheden et al 2012). Two types of adhesive can be distinguished: the primary cement, produced while the animal is attached to a substratum, and the secondary cement, secreted when the animal is injured or detached Kamino et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The holdfast system of the barnacle differs from that of mytilid mussels and sabellariid polychaetes by the lack of a detectable L-DOPA system and the slow curing process of the adhesive (Naldrett 1993;Kamino et al 1996;Kamino 2010;Nicklisch & Waite 2012). Barnacle cement is produced by unicellular glands throughout the lifetime of the animal in accordance with its moulting cycle Fyhn & Costlow 1976;Jonker et al 2012;Zheden et al 2012). Two types of adhesive can be distinguished: the primary cement, produced while the animal is attached to a substratum, and the secondary cement, secreted when the animal is injured or detached Kamino et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is unique among the barnacles due to the amount and morphological structure of the cement it produces. It secretes layer by layer an excess amount of foam-like cement (Zheden et al 2012) (Figure 1 and Supplementary Figure S1). [Supplementary material is available via a multimedia link on the online article webpage.]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosima fascicularis is characterized by the presence of thin and delicate plates, and a ball-shaped body surrounding the distal part of the peduncle (Darwin, 1852;Young, 1990;Hinojosa et al, 2006). The ball is secreted from the cement glands and consists of numerous gas-filled chambers that serve as a flotation device to keep the organism at the seaair interface (Darwin, 1852;Boetius, 1952Boetius, -1953Zheden et al, 2012). Additionally, D. fascicularis exhibits a blue coloration typically observed in other euneustonic species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These authors determined that the cement is composed mainly of acid proteins and differs from other cirripeds (balanids) having a distinctly higher proportion of glutamic acid and smaller quantities of lysine, histidine and tyrosine which could be providing a spongy mass which will act as a float rather than a strong adhesive structure. This cement usually forms an oval, whitish-beige foam-like float that may enclose the initial substratum (Zheden et al, 2012). Cheng & Lewin (1976) observed that the majority of the Dosima recorded on the coast of California were attached to a noticeable substrate as feathers or brown algae or unattached (at least noticeably) with a minor proportion attached to tar lumps.…”
Section: Introductionmentioning
confidence: 99%